Advances in Understanding and Managing Alzheimer's Disease: From Pathophysiology to Innovative Therapeutic Strategies - Rathee, Sunny; Sen, Debasis; Pandey, Vishal; Jain, Sanjay K. (Current Drug Targets, 2024)
Alzheimer's disease (AD) is a debilitating neurodegenerative disorder characterized by the presence of amyloid-β (Aβ) plaques and tau-containing neurofibrillary tangles, leading to cognitive and physical decline. Representing the majority of dementia cases, AD poses a significant burden on healthcare systems globally, with onset typically occurring after the age of 65. While most cases are sporadic, about 10% exhibit autosomal forms associated with specific gene mutations. Neurofibrillary tangles and Aβ plaques formed by misfolded tau proteins and Aβ peptides contribute to neuronal damage and cognitive impairment. Currently, approved drugs, such as acetylcholinesterase inhibitors and N-methyl D-aspartate receptor agonists, offer only partial symptomatic relief without altering disease progression. A promising development is using lecanemab, a humanized IgG1 monoclonal antibody, as an immune therapeutic approach. Lecanemab demonstrates selectivity for polymorphic Aβ variants and binds to large soluble Aβ aggregates, providing a potential avenue for targeted treatment. This shift in understanding the role of the adaptive immune response in AD pathogenesis opens new possibilities for therapeutic interventions aiming to address the disease's intricate mechanisms. This review aims to summarize recent advancements in understanding Alzheimer's disease pathophysiology and innovative therapeutic approaches, providing valuable insights for both researchers and clinicians.
Keywords: Alzheimer’s disease